(untitled) (Research, Society and Development, 2020)
Objective: This article aims to develop an analysis through an integrative review on the relationship between women’s health and obstetric violence in the context of childbirth and birth in Brazil. Method: This is an integrative review, whose research method is an essential tool, as it allows analysis through a literature review in a broad and systematic way, in addition to disseminating scientific data produced by other authors. Results: Within the hospital environment, pregnant women are received in a hostile environment, where verbal violence is practically certain in their first contacts. Hospital routines cause isolation of parturients and their families and even companions, with inappropriate procedures such as vaginal touching without the necessary and repetitive care, the restriction of obstetric milk. Conclusion: it appears that the proposed reflections sought to elucidate the main reasons and to raise the awareness of everyone involved, from professionals working with assistance to class entities to the theme.